A Study of Knowledge, Attitudes and Practices Regarding Contraceptive Services Among Health Workers in Sangli District of Maharashtra, India - Girish M Chavan; Vivek B Waghachavare; Manohar S Chavan; Vishwajeet M Chavan; Alka D Gore; Girish B Dhumale (Medsci Publications, 2014)
Background: Government Health workers play important role in awareness and acceptance of contraceptives. Hence review of their functioning is essential. In this context this study was conducted to assess the knowledge, attitude and practices regarding contraceptive services among health workers. Methodology: It is a Cross-sectional study conducted over a period of 3 months. Calculated Sample size was 150 with simple random sampling technique. Clearance from the institutional ethical committee and concerned authorities of the college had been taken for the study. Study tool was Pre-designed self administered Questionnaire, for assessing knowledge, attitude and practices regarding contraceptive services among Government Health workers from randomly selected Primary Health Centers (PHCs). Results: Of the 153 subjects, mean scores for knowledge, attitude and practices regarding contraceptive services were respectively 12.29, 9.58 and 11.27. There was no significant difference in knowledge of those under 35 yrs and those above it; but there was statistically significant difference in attitude and practices regarding contraceptive services. The knowledge and practices regarding contraceptive services regarding emergency contraception were associated with designation with ANM faring better in it. Conclusion: Although the health workers fared well in knowledge, attitude and practices regarding contraceptive services, there is room for further improvement.